Mechanical, Structural, and Thermal Qualification of Solid Oxide Elextrolysis for Oxygen Production from Mars Atmosphere Carbon Dioxide. (30th May 2017) - Hartvigsen, Joseph; Elangovan, S; Elwell, Jessica; Larsen, Dennis; Clark, Laurie M.; Meaders, Thomas
Abstract : The NASA Mars2020 mission will land a Curiosity class rover on Mars with a set of seven new science instruments (1). One of these instruments, MOXIE, the Mars Oxygen ISRU (In Situ Resource Utilization) Experiment, will demonstrate oxygen production by solid oxide electrolysis of Mars atmosphere CO2 . The rover host platform for the MOXIE project imposes severe constraints on mass, volume, peak power and total cycle energy, but it also offers an early opportunity to demonstrate non-terrestrial ISRU. The fundamental operating principles and materials of the Mars ISRU application are no different than for the more common terrestrial hydrogen and synfuel applications. However, the environments the device will be subjected to in reaching Mars, and while operating on the Martian surface, create the need for some unique and highly rigorous qualification testing. Ceramatec has developed and qualified the Solid OXide Electrolysis (SOXE) device for MOXIE.